THE COACH'S ROLE IN PERSIGAR PLAYERS' DECISION MAKING DURING THE MATCH - Arif Budiman; Z. Arifin; Asep Angga Permadi (Universitas Hamzanwadi, 2026)
Decision-making ability is a crucial cognitive factor in modern soccer that determines a player’s success in choosing the right course of action under the pressure of a match. However, research examining the relationship between the coach’s role and the decision-making ability of soccer players in Indonesia remains limited. This study aims to analyze the relationship between the coach’s role and the decision-making ability of Persigar Garut players. The study employs a quantitative approach with a correlational design. The sample consisted of 31 players selected using total sampling. Data were collected using an online questionnaire, with the Leadership Scale for Sport (LSS) to measure the coach’s role and an instrument based on the concepts of Roca, Ford, & Memmert to measure decision-making. Data analysis used the Spearman correlation test because one of the variables was not normally distributed (Shapiro-Wilk, p = 0.045). The results showed a correlation coefficient of 0.443 with a significance value of 0.012 (p < 0.05), indicating a positive, significant, and moderate relationship. The coefficient of determination (R²) was 19.6%. indicates the contribution of the coach’s role to decision-making, while 80.4% is influenced by other factors. The conclusion of this study is that there is a significant relationship between the coach’s role and the decision-making ability of Persigar Garut players.